Hemp Extract (Extractum Cannabis) in the Treatment of Gastrointestinal Distress and Dyspepsia: Historical Insights from Barcelona, Spain - Kenzi Riboulet-Zemouli; Josep Allué Creus (Pharmaceuticals)
This study explores the trajectory of interest in and use of Extractum Cannabis (hemp extract, i.e., extract of Cannabis sativa L.) for the symptomatic treatment of minor gastrointestinal distress and dyspepsia in nineteenth- and early twentieth-century Barcelona (Catalonia, Spain) prior to 1939, through a review of primary sources. The objective of this paper is to present a historical pharmaceutical and applied review of the medical use of the hemp genus (Cannabis L.) prior to its prohibition, thereby contributing to its recognition as a medicinal product. The information provided demonstrates evidence of the medicinal use of cannabis within the historical context studied. The interactions between this legacy medical use and the contemporary body of pharmacological and toxicological knowledge (on hemp, its constituents, and the endocannabinoid system in gastrointestinal and stomach disorders) are discussed, providing new possible clinical perspectives. Within its limitations—including the scope, limited accessibility to, and varying quality of archives—this research contributes to a more granular understanding of the historical embeddedness of psychoactive hemp medicines in northeastern Spain, suggesting that medical and pharmaceutical traditions could play a role in informing contemporary approaches to “medical marijuana”.